Risky sexual behaviours and the associated factors among undergraduates of the University of Jaffna - Dassanayaka, D.M.C.D.; Gunarathna, B.G.S.M.; Sathees, S.; Kajavinthan, K. (Faculty of Allied Health Sciences, University of Jaffna, Sri Lanka., 2023)
Introduction: Sexual behaviors refers to a wide range of actions that people use to express their sexual orientation. It ranges from solitary behaviors such as masturbation to partnered sex like intercourse or non-penetrative sex. The behaviors with potential to harm a person’s health are recognized as risky sexual behaviors. Objective: To assess the risky sexual behaviors and its associated factors among undergraduates of the University of Jaffna. Methodology: A descriptive cross-sectional study was conducted among 428 undergraduates, at the University of Jaffna. A self-administered questionnaire was used to collect the data. Data were analyzed by using Statistical Package of Social Science (SPSS) version 26. The association of risky sexual behaviors with the Socio - demographics, and other factors was determined by chi-Square test. Results: Among the 428 prospective participants, almost half were males (50.9%). And most of them (66.6%) were under the age of 24 years. Among them 42.5% were Buddhists, and 36.9% were Hindus. Only a few students (15%) were living at their houses with their parents or spouse. More than half of the students were studying in their first and second years of study in their respective Faculties. Regarding their sexual practices, 26.6% of them were sexually active. Among them 15.2% were engaged in any type of risky sexual behavior. The following factors were associated with the exposure to risky sexual behaviors; Gender (p=0.001), Faculty they belong (p=0.002), monthly income (p=0.019), cigarette smoking (p=0.001) and the habit of accessing pornography (p=0.001), chronic worries in life (p=0.047), peers’ influence on sexual activity (p=0.001). Conclusion: The prevalence of risky sexual behaviors among undergraduates seems higher compared to other national studies. And it is associated with several factors. Interventions to abstain from risky sexual behaviors among the students are mandatory. The associated factors identified should be considered while planning such activities.
Keywords: Risky sexual behaviors; Undergraduates; Sexual health